Análise de componentes principais aplicada ao estudo termoanalítico de sementes e a produção vegetal do Mandacaru (Cereus jamacaru DC.) - Morais, Lécia Pinto Ferreira de (2018)
Cereus jamacaru DC, popularly called mandacaru, is a columnar cactus of the family Cactaceae, found spontaneously and dispersed in the Caatinga, utilized by the sertanejo as a forage plant. However, ethno pharmacological literature describes its application in the fight against or prevention of various diseases, such as respiratory diseases, renal, stomatitis ulcers, arterial hypertension, enteritis and rheumatism. The objective of this work was to study the characterization of seeds and juvenile plants of C. jamacaru, grown under controlled conditions of production using multivariate statistical techniques. In this perspective, the work was carried out with collecting fruits of six matrices (M) of the species, in a similar stage of maturation, in two Semiarid sites Paraibano, Sumé (M1, M2, and M3) and Monteiro (M4, M5, and M6) for the biometric characterization of fruits and seeds of the species. The seeds of C. jamacaru were used as feedstock for thermoanalytical and vegetable production studies with the application of main component analysis (PCA) in the original data obtained. The following were determined: moisture content; ashes: thermogravimetry (TG) in the heating ratios 5, 10, 20, and 40 oC min-1 for the atmosphere of synthetic air and heating ratio 10 oC min-1 for nitrogen atmosphere; kinetic parameters and differential thermal analysis (DTA), 10 oC min-1. Through the PCA, the biometric variability of the fruits and seeds of the studied matrices was evidenced. Analyzing the TG curves at the 10 oC min-1 heating rate, there were five mass degradation events in the oxidative atmosphere and four mass degradation events in inert atmosphere, except for M1 that presented five mass degradation events also in atmosphere of nitrogen. The temperature and mass loss of the two main stages of degradation varied among the matrices. The DTA curves showed three exothermic events for M1, M2, M3, M5, and M6 crushed seeds with peak ranging from 354.0–358.9 °C, 492.9–508.1 °C and 509.8–523.7 °C, and M4 presented four exothermic events. The DTA curves for whole seeds of M2 and M5 revealed two exothermic events being M2 with peak ranging between 349.2– 355.8 oC and 538.3–543.7 oC, and M5 with peak ranging between 361.8–374.0 oC and 537.7– 551.4 °C. PCA applied to TG in the fourth heating reasons (oxidative atmosphere) indicated similarity between the thermal profiles of the matrices. The PCA of the vegetal production indicated a pattern for the juvenile individuals of M6 in the parameters: greater number of emergence, less days to emerge, greater height of the aerial part and diameter at the level of the ground; in addition to allowing differentiations between the groupings of individuals generated from each of the matrices monitored by the graphic visualization. The results obtained in this study indicated that the application of PCA for the evaluation of the thermal profile of seeds of C. jamacaru, specifically in TG, did not provide standardized visualization among the evaluated matrices, however, for the evaluation of vegetable production, revealed to be an excellent tool for the study of differentiation and characterization among the C. jamacaru matrix, evaluated, allowing the determination of the matrix with higher productive potential, with M6 having the best performance in plant production for this species.